DURATION OF GRANITOID MAGMATISM IN PERIPHERAL PARTS OF LARGE IGNEOUS PROVINCES (BASED ON 40AR/39AR ISOTOPIC STUDIES OF ALTAI PERMIAN-TRIASSIC GRANITOIDS) - O. A. Gavryushkina; A. V. Travin; N. N. Kruk (Геодинамика и тектонофизика, 2017)
In large igneous provinces (LIP) of fold areas, granitoid rocks are dominant, while mantle-derivated rocks play a subordinate role in rock formation. If magma emissions are impulsive, it may take 25–30 million years for a LIP to form and take shape. In this paper, we present the results of 40Ar/39Ar isotopic studies of Permian-Triassic granitoids in the Altai region, Russia, and clarify the evolution of this region located at the periphery of the Siberian LIP. These granitoids are very diverse and differ not only in their rock set, but also in the composition features. In the study region, the granodiorite-granite and granite-leucogranite association with the characteristics of I- and S-types as well rare metal ore-bearing leucogranites are observed along with gabbro- and syenite-granite series, including mafic and intermediate rocks with the A2-type geochemical features. The 40Ar/39Ar data obtained in our study suggest that most of the studied granitoids intruded within a short period of time, 254–247 Ma. This timeline is closely related to the formation of granitoids in theKuznetsk basin and dolerite dikes in the Terekta complex (251–248 and 255±5 Ma, respectively), as well as intrusions of lamproite and lamprophyre dikes of the Chuya complex (245–242 and 237–235 Ma). Thus, we conclude that the Altai Permian-Triassic granitoids are varied mainly due to the evolution of mafic magmatism.